2015
DOI: 10.2147/dddt.s86750
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between UGT1A1*6/*28 polymorphisms and severe toxicities in Chinese patients with pancreatic or biliary tract cancer treated with irinotecan-containing regimens

et al.

Abstract: PurposeThe aim of this retrospective study was to investigate the relationship between UGT1A1 polymorphisms and toxicities in Chinese patients with pancreatic or biliary tract cancer receiving irinotecan-containing regimens as the second- or third-line chemotherapy.Patients and methodsA total of 36 patients with unresectable pancreatic cancer and 12 patients with unresectable biliary tract cancer were included. Approximately 33 patients were treated with FOLFIRI regimen, a chemotherapy regimen, where FOL stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…However, UGT1A1 genotype was associated with an increased risk of grade 1-4 and severe neutropenia at the first and second cycle. Similar to the study by Yang et al 29 , UGT1A1*28 and *6 were significantly associated with higher incidence of grade 3-4 neutropenia. www.nature.com/scientificreports/ A meta-analysis by Han et al 30 found that Asian cancer patients with UGT1A1*28 and *6 are at increased risk of irinotecan-induced neutropenia.…”
Section: Discussionsupporting
confidence: 88%
“…However, UGT1A1 genotype was associated with an increased risk of grade 1-4 and severe neutropenia at the first and second cycle. Similar to the study by Yang et al 29 , UGT1A1*28 and *6 were significantly associated with higher incidence of grade 3-4 neutropenia. www.nature.com/scientificreports/ A meta-analysis by Han et al 30 found that Asian cancer patients with UGT1A1*28 and *6 are at increased risk of irinotecan-induced neutropenia.…”
Section: Discussionsupporting
confidence: 88%
“…Applying the exclusion criteria, 195 articles were removed and the remaining 105 full‐text articles were assessed in depth in line with the predetermined eligibility criteria. Finally, 42 articles were included in the meta‐analysis for assessing the associations of UGT1A1*6/UGT1A1*28 or ABCC2 c.3972C>T with irinotecan‐induced severe toxicities 12,14,21–24,26–31,34,35,48–75 . The complete selection process for the articles following PRISMA guidelines is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] However, some studies did not find any significant association of UGT1A1*6 genetic polymorphism and irinotecan-driven toxicities. 18,26 When patients inherit both of these polymorphisms (UGT1A1*6 and UGT1A1*28), irinotecan toxicity may be exacerbated profoundly due to combined genetic effects as evidenced in some studies, 14,[26][27][28] although the results from other studies are again inconclusive and inconsistent. 18,[29][30][31] In these controversial clinical situations, it is also important to note that in addition to the UGT1A1 enzyme, irinotecan, SN-38, and SN-38G are transported out of the cell into bile by members of the ATP-binding cassette (ABC) transporter family, especially ABCC2 encoded by the ABCC2 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Following exclusion criteria, 195 articles were removed, and the rest 106 full-texts articles were assessed in depth following eligibility criteria. Finally, 42 articles were included in this meta-analysis for assessing the associations ofUGT1A1*6/*28 or ABCC2 c.3972C>T with irinotecan induced severe toxicities [12,14,21,[22][23][24][26][27][28][29][30][31]34,35,]. The complete selection process of articles following PRISMA guidelines is shown in Figure 1.…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
“…When patients inheriting both of these polymorphisms (UGT1A1*6 and UGT1A1*28), the toxicities of irinotecan may be exacerbated profoundly due to combined genetic effects as evidenced in some studies [14,[26][27][28] although the results are again inconclusive and inconsistent as found in other studies [18,[29][30][31]. In these controversial clinical situations, it is also important to noted that in addition to the UGT1A1 enzyme, irinotecan, SN-38 and SN-38G are transported out of the cell into bile by members of the ATP-binding cassette (ABC) transporter family especially ABCC2 encoded by theABCC2 gene [32,33].…”
Section: Introductionmentioning
confidence: 99%